Gender differences in santri’s reading attitude and motivation - Banatul Murtafi'ah; Nur Hidayanto Pancoro Setyo Putro (Universitas Islam Sultan Agung, 2020)
A considerable amount of studies has explored gender differences in reading attitude and motivation among students in both elementary and secondary school levels. However, none of them is concerned with English reading attitude and motivation among santri or students living at Islamic boarding school in which gender segregation is applied. This study attempts to investigate santri’s reading attitude and reading motivation based on their gender. Three hundred and nineteen students at pesantren-based senior high schools in Yogyakarta Special Region province participated in the study by completing both reading attitude questionnaires and motivational reading questionnaire (MRQ). The results showed that there were significant differences among female and male santris in terms of reading attitude and motivation. The independent sample t-test revealed that female students reported statistically significant higher attitude in both academic and recreational reading than male students. Similarly, female students also reported higher reading motivation in three dimensions of MRQ, i.e. reading involvement, importance of reading, and competition in reading than male student. Likewise, regression analysis showed that gender could predict santri’s reading attitude and motivation. This study, therefore, confirmed a consistent finding from the previous studies revealing that female students had higher reading attitude and motivation than male students.